'The Storying Spiral': a narrative-dramatic approach to life story therapy with adoptive/foster families and traumatised children. Issue 2 (4th May 2019) - Moore, Joan Elizabeth
ABSTRACT: 'The Storying Spiral' is a new model called 'Theatre of Attachment', used with fostered or adopted children in their homes. It focuses on encouraging communication through dramatic play. Examples from the author's original doctoral research [Moore, J. (2018). Using story and drama with adoptive and foster families in their homes (unpublished PhD, Leeds Beckett University)] illustrate how trauma symptoms can be reduced and positive attachment encouraged through dramatization of scenes from the children's past life. The model grew from the author's earlier work [Moore J. (2006). Theatre of attachment; using drama to facilitate attachment in adoption. Adoption and Fostering, 30 (2), 64–73]. As the study children were aged 6–9 years, to show how this intervention works with older children a case study demonstrates its application with a 13-year-old boy. The approach was effective in significantly reducing his trauma symptoms, raising his self-esteem and securing his attachment to long-term foster carers.